Advanced Predictive and AI-Based Converter Control Strategies for AC and DC Microgrids - Khan, Hussain Sarwar (Vaasan yliopisto, 2026)
The increasing penetration of inverter-based distributed energy resources (DERs) is reshaping modern power systems. However, it also introduces major challenges to their operation and stability. In particular, the stability of modern power systems is affected by low inertia, nonlinear load characteristics and limited fault current contribution. Conventional linear controllers are widely used, but have inherent shortcomings, including slow transient response, poor disturbance rejection and an inability to effectively handle nonlinearities or parametric uncertainties. To address these limitations, this dissertation develops and validates advanced predictive and artificial intelligence (AI)-based control strategies for AC and DC islanded microgrids operating at low-voltage levels. First, this dissertation introduces an improved finite control set model predictive control (FCS–MPC) strategy for inverter-based DERs in AC microgrid. A dual-objective cost function is proposed to simultaneously regulate the output voltage and limit the fault current under symmetrical fault conditions. A two-step-ahead prediction method achieves reduced switching frequency, improved steady-state accuracy and robustness against parametric variations. Furthermore, a predictive hierarchical control architecture was implemented. The stability of the proposed scheme is formally established through Lyapunov analysis, while validation through MATLAB/Simulink simulations and FPGA-in-the-loop (FIL) verifies superior performance compared to conventional techniques. Second, this dissertation advances AI-based control in DC microgrids. An artificial neural network (ANN) voltage controller was developed using datasets generated by the FCS–MPC, which preserves both a fast transient response and robustness under nonlinear constant power loads. Additionally, a reduced-sensor ANN controller is proposed that relies solely on voltage measurements, providing a cost-effective and scalable solution for real-world implementation. Both approaches are validated through real-time hardware-in-the-loop (HIL) testing, demonstrating reliable voltage regulation in multibus DC microgrid environments. Overall, this dissertation contributes a comprehensive framework of predictive and AI-based controllers that enhance the reliability, efficiency and scalability of islanded microgrids. By bridging theoretical modelling, real-time validation and open research practices, this work provides a pathway for a resilient, low-carbon power system in the future.

Invertteripohjaisten hajautettujen energiaresurssien lisääntynyt hyödyntäminen tuo mukanaan merkittäviä haasteita sähkövoimajärjestelmän toimintaan ja stabiiliuteen. Erityisesti haasteita aiheuttavat matala inertia, epälineaariset kuormat sekä rajoitettu vikavirran syöttö. Perinteisiä lineaarisia säätimiä käytetään laajasti, mutta niillä on luontaisia puutteita, kuten hidas transienttivaste, heikko häiriöiden sietokyky ja rajoittunut kyky käsitellä epälineaarisuuksia tai parametriepävarmuuksia. Näiden rajoitusten ratkaisemiseksi tässä väitöskirjassa kehitetään ja validoidaan edistyneitä ennakoivia ja tekoälypohjaisia säätöstrategioita sekä vaihto- (AC-) että tasasähkö (DC-) mikroverkoille. Ensiksi väitöskirjassa esitellään parannettu mallipohjainen ennakoiva säätö, FCS–MPC, invertteripohjaisille hajautetuille energiaresursseille. Kaksitavoitteinen kustannusfunktio mahdollistaa samanaikaisesti lähtöjännitteen säätämisen ja vikavirran rajoittamisen symmetrisissä vikatilanteissa. Kahden askeleen ennustemenetelmä mahdollistaa pienemmän kytkentätaajuuden, paremman vakiotilan tarkkuuden ja paremman robustisuuden parametrimuutoksia vastaan. Lisäksi toteutetaan ennakoiva hierarkkinen säätöarkkitehtuuri. Ehdotetun menetelmän stabiilius osoitetaan Lyapunovin analyysin avulla, ja perinteisiä menetelmiä parempi suorituskyky vahvistetaan MATLAB/Simulink-simulaatioilla sekä FPGA-in-the-loop-testauksella. Toiseksi väitöskirja edistää tekoälypohjaista säätöä tasajännite mikrosähköverkoissa. Keinotekoinen neuroverkkoon (ANN) perustuva jännitteenohjain kehitetään FCS–MPC:n tuottaman aineiston avulla, mikä mahdollistaa nopean transienttivasteen ja robustin säädön epälineaarisilla vakio-tehokuormilla. Lisäksi ehdotetaan vähennettyyn anturimäärään perustuva ANN-säätö, joka käyttää vain jännitemittauksia, tarjoten kustannustehokkaan ja skaalautuvan ratkaisun käytännön toteutukseen. Molemmat lähestymistavat validoidaan reaaliaikaisilla laitteistosilmukka (HIL) testeillä, jotka osoittavat luotettavan jännitteen säädön usean solmupisteen DC-verkoissa. Kaiken kaikkiaan tämä väitöskirja tarjoaa perustan ennakoiville ja tekoälypohjaisille säätimille, jotka parantavat mikroverkkojen luotettavuutta, tehokkuutta ja skaalautuvuutta. Yhdistämällä teoreettisen mallinnuksen, reaaliaikaisen validoinnin ja avoimen tutkimuskäytännön työ tarjoaa polun kohti resilienttiä ja vähähiilistä tulevaisuuden invertteripohjaista sähkövoimajärjestelmää.
Keywords: electrical engineering; technology; microgrids; forecasts; electrical power networks; distribution of electricity; energy; fi=Sähkötekniikka|en=Electrical Engineering|